PERFORMANCE ANALYSIS OF 4-OUTLETS SPRAY AERATOR FOR PROCESSING OF INDIGOFERA LEAVES (Indigofera Tinctoria Linn) BECOMES NATURAL DYE SUBSTANCES (Universitas Negeri Semarang, 2017)
The commonly known natural dye substance processing for traditional clothes, such as batik and tenun (woven cloth) is fermentation. The fermentation process can specifically be continued with extraction to produce indigo paste. The process can be done mechanically, i.e. by stirring process, and chemically. In order to accelerate the production, manual process of aeration can be substituted with jet-spray aerator. The aerator prototype which has been developed is acrylic aerator tube with diameter of 240 mm and thickness of 5 mm. The tube was made 1 m long to provide with a sufficient space for indigo foam. Its bottom part is completed with spiral air hose having five small holes of 0.2, 0.4, and 0.6 mm diameter uniformly located along the height of solution in the tube. The aerator was designed for the 10 litters of fermentation solution of 1 kilogram indigofera leaves. Based on the mass of indigo paste produced, the optimum working condition of the aerator is achieved on 3.8 m/sec air velocity and supply pressure of 2 bar with duration of 60 minutes. The aeration test indicated operational characteristic was quite good, i.e. Oxygen Transfer Rate (OTR) of 3.6 kg/hour, Aeration Efficiency (AE) of 4.8 kg/kWh and factual Oxygen Transfer Efficiency (OTE) of 44%.